5G service delivery platform: 360 VR vertical as an example. Issue 6 (23rd June 2020) - Hänsge, Kay; Trossen, Dirk; Robitzsch, Sebastian; Boniface, Michael J.; Phillips, Stephen C.
Abstract : Operators have been adopting the cloud‐native paradigm for the roll‐out of 5G architecture. With it goes the introduction of the service‐based architecture as a key design pattern for realizing future control‐ and ultimately user‐planes of mobile networks. The main benefits of this new design pattern are increased flexibility, meaning new business cases may be addressed while maintaining competitive cost levels, and also the ability to realize use cases which historically have required the full breadth of infrastructure level knowledge. We present a realization of a service delivery platform entirely built upon service‐based architecture principles. Abstract : The service‐based architecture is a key design pattern for realizing future control‐ and ultimately user‐planes of mobile networks. The authors Kay Hänsge, Dirk Trossen, Sebastian Robitzsch, Michael J. Boniface, Stephen C. Phillips present a realization of Cloud‐native 5G Service Delivery Platform offering increased flexibility with competitive cost levels, and also the ability to realize use cases which historically have required the full breadth of infrastructure level network slicing.